THEORETICAL AND METHODOLOGICAL ANALYZING OF CONTENT CHARACTERISTICS OF AN INDIVIDUAL’S PERFECTIONISM - Karina Vitaliivna Klenina (Insight: the psychological dimensions of society, 2019)
Abstract: The paper indicates that universal globalization, social transformations, complication of relationship areas, continuous growth of requirements to efficient functioning of an individual in society inevitably provoke increasing formation and spreading of such a psychological phenomenon as perfectionism. It highlights that this tendency has caused a stronger inclination to perfectionism of young people nowadays than that of their coevals in the ’90s of the past century.Purpose: to analyze basic theoretical and methodological approaches to the understanding of the concept “perfectionism”; to determine the key tasks of the research on an individual’s perfectionism; to distinguish its basic characteristics.Methods: theoretical analyzing, synthesizing, systematization and generalization of scientific primary sources.Results: the study analyzes basic theoretical and methodological approaches to the understanding of the concept “perfectionism”; it distinguishes its basic characteristics; it suggests the logic of theoretical and methodological search, which made it possible to outline the algorithm of the research on psychology of an individual’s perfectionism. The paper finds out that the first phenomenological descriptions of perfectionism of psychological nature were related to the tendency of an individual to set extremely high standards, preventing him or her from being pleased with their results. It determines that the emphasis on searching for the ways, means and techniques of efficient implementation of progressive technologies and innovations while changing from “undesirable / desirable trait” in the context of the research on personal characteristics and qualities of a subject of activeness is a methodologically important aspect in the research on the suggested phenomenon. The study looks at the views of the British and Canadian groups of scientists who created their multidimensional models.Conclusions: the paper outlines the understanding of the depth and complication of a psychological phenomenon of an individual’s perfectionism. It traces the tendency of the ambivalence of views on the problem in the genesis of studying this concept. The study determines that the majority of scientists are still inclined to destructive influence of this phenomenon.